2008
DOI: 10.1186/cc6248
|View full text |Cite
|
Sign up to set email alerts
|

Dalbavancin safety in the phase 2/3 clinical development program

Abstract: IntroductionIn order to find out the frequency rates of domestic and wild animal bites as well as the evaluation of the prevalence rates of rabies disease in the human population in the Province of Kerman, a retrospective study was designed to analyze statistically the collected recorded data related to this project. Methods This study was conducted within the framework of MPVM student research projects by means of collaboration between

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2008
2008
2008
2008

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…Overall success rates were similar between the 2 treatment arms at end of therapy and TOC visit, thus conferring clinical relevance of noninferiority [36]. In other studies [37,38], dalbavancin was compared with linezolid, vancomycin, and cefazolin for the treatment of S. aureus SSTI. In the microbiologically evaluable population, dalbavancin was associated with an eradication rate of 90%, compared with 82% for vancomycin.…”
Section: Clinical Efficacymentioning
confidence: 69%
See 1 more Smart Citation
“…Overall success rates were similar between the 2 treatment arms at end of therapy and TOC visit, thus conferring clinical relevance of noninferiority [36]. In other studies [37,38], dalbavancin was compared with linezolid, vancomycin, and cefazolin for the treatment of S. aureus SSTI. In the microbiologically evaluable population, dalbavancin was associated with an eradication rate of 90%, compared with 82% for vancomycin.…”
Section: Clinical Efficacymentioning
confidence: 69%
“…There is no known evidence of renal or hepatic toxicity related to dalbavancin therapy [38]. In clinical trials thus far, subjects receiving dalbavancin versus placebo reported similar rates of pyrexia and headaches [25].…”
Section: Safetymentioning
confidence: 99%
“…90,91 Dalbavancin (Pfizer), another compound structurally similar to the glycopeptide teicoplanin (which is approved for use in Europe), recently completed Phase III clinical trials for the treatment of complicated skin and soft-tissue infections, as well as a Phase II trial for catheterrelated bloodstream infections. [92][93][94][95] The agent demonstrates activity against MRSA and other grampositive organisms. 26,27,[40][41][42][43][44][45][46][47][48][49] Dalbavancin has an extended half-life (9-12 days), which may allow for weekly administration.…”
Section: Place In Therapymentioning
confidence: 99%
“…None of these required intervention. No effect on prolongation of the QT interval has been demonstrated [75] . Furthermore, administration of dalbavancin has not led to any reported cases of 'red man syndrome', as is the case with vancomycin.…”
Section: Safety and Tolerabilitymentioning
confidence: 99%
“…Furthermore, administration of dalbavancin has not led to any reported cases of 'red man syndrome', as is the case with vancomycin. Dalbavancin has not shown an incidence of serum creatinine elevation and, thus, may show a negligible risk of nephrotoxicity associated with its use [39,61,71,73,75] . A study by Nord et al [76] evaluated dalbavancin's effect on the intestinal microflora.…”
Section: Safety and Tolerabilitymentioning
confidence: 99%